Laser ablation after stereotactic radiosurgery: a multicenter prospective study in patients with metastatic brain tumors and radiation necrosis - Ahluwalia, Manmeet; Barnett, Gene H; Deng, Di; Tatter, Stephen B; Laxton, Adrian W; Mohammadi, Alireza M; Leuthardt, Eric; Chamoun, Roukoz; Judy, Kevin; Asher, Anthony; Essig, Marco; Dietrich, Jorg; et al. (Journal of neurosurgery, 2019)
Laser Ablation After Stereotactic Radiosurgery (LAASR) is a multicenter prospective study of laser interstitial thermal (LITT) ablation in patients with radiographic progression after stereotactic radiosurgery for brain metastases. Patients with a Karnofsky Performance Scale (KPS) score ≥ 60, an age > 18 years, and surgical eligibility were included in this study. The primary outcome was local progression-free survival (PFS) assessed using the Response Assessment in Neuro-Oncology Brain Metastases (RANO-BM) criteria. Secondary outcomes were overall survival (OS), procedure safety, neurocognitive function, and quality of life. Forty-two patients—19 with biopsy-proven radiation necrosis, 20 with recurrent tumor, and 3 with no diagnosis—were enrolled. The median age was 60 years, 64% of the subjects were female, and the median baseline KPS score was 85. Mean lesion volume was 6.4 cm3 (range 0.4–38.6 cm3). There was no significant difference in length of stay between the recurrent tumor and radiation necrosis patients (median 2.3 vs 1.7 days, respectively). Progression-free survival and OS rates were 74% (20/27) and 72%, respectively, at 26 weeks. Thirty percent of subjects were able to stop or reduce steroid usage by 12 weeks after surgery. Median KPS score, quality of life, and neurocognitive results did not change significantly for either group over the duration of survival. Adverse events were also similar for the two groups, with no significant difference in the overall event rate. There was a 12-week PFS and OS advantage for the radiation necrosis patients compared with the recurrent tumor or tumor progression patients. In this study, in which enrolled patients had few alternative options for salvage treatment, LITT ablation stabilized the KPS score, preserved quality of life and cognition, had a steroid-sparing effect, and was performed safely in the majority of cases.